2011
DOI: 10.1152/ajpgi.00461.2010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of squamous esophageal cells resistant to bile acids at acidic pH: implication for Barrett's esophagus pathogenesis

Abstract: Barrett's esophagus (BE) is a premalignant condition, where normal squamous epithelium is replaced by intestinal epithelium. BE is associated with an increased risk of developing esophageal adenocarcinoma (EAC). However, the BE cell of origin is not clear. We hypothesize that BE tissue originates from esophageal squamous cells, which can differentiate to columnar cells as a result of repeated exposure to gastric acid and bile acids, two components of refluxate implicated in BE pathology. To test this hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…Next, we found the role of EGFR in CDX2 induction not only by AG1478 but also by siRNA specific for human EGFR, since the treatment of AG1478, commonly used as an EGFR inhibitor by inhibiting EGFR tyrosine kinase, might have nonspecific effects on EGFR [32,36]. The roles of EGFR in CDX2 induction were supported by previous studies [5,9,38] about the induction of CDX2 through the activation of EGFR by bile acids via both ligand-dependent and ligand-independent mechanisms. Taken together, we demonstrated that the exposure to NO or peroxynitrite ligand-independently enhanced CDX2 expression though the activation of EGFR in KYSE30.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Next, we found the role of EGFR in CDX2 induction not only by AG1478 but also by siRNA specific for human EGFR, since the treatment of AG1478, commonly used as an EGFR inhibitor by inhibiting EGFR tyrosine kinase, might have nonspecific effects on EGFR [32,36]. The roles of EGFR in CDX2 induction were supported by previous studies [5,9,38] about the induction of CDX2 through the activation of EGFR by bile acids via both ligand-dependent and ligand-independent mechanisms. Taken together, we demonstrated that the exposure to NO or peroxynitrite ligand-independently enhanced CDX2 expression though the activation of EGFR in KYSE30.…”
Section: Discussionsupporting
confidence: 72%
“…Concerning the role of NO in EGFR activation, we showed that the treatment of NOC7, peroxynitrite or SIN-1 induced EGFR phosphorylation in a ligandindependent manner and that the effects of treatment with NOC7 were significantly inhibited by Carboxy-PTIO in a dose-dependent manner. The mechanisms in this signaling were described in previous studies [34,35,38,44] demonstrating that exogenous NO might induce the trans-activation of tyrosine residue in cytoplasm and that exogenous peroxynitrite might activate extracellular signal-regulated kinases in the EGFR signal transduction pathway. Next, we found the role of EGFR in CDX2 induction not only by AG1478 but also by siRNA specific for human EGFR, since the treatment of AG1478, commonly used as an EGFR inhibitor by inhibiting EGFR tyrosine kinase, might have nonspecific effects on EGFR [32,36].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…IL-8 and IL-1␤ have been shown to be upregulated, even in endoscopy-negative patients (11,14,15,20,26,28). In vitro experiments also showed that exposure of human esophageal epithelial cells to acid or bile acid activated the NF-B pathway and upregulated IL-6 and IL-8 (10,12,17,35) as a function of the degree of acidity and exposure time (13). In this study, activation of the NF-B pathway was observed in the esophageal epithelium with duodenal or mixed reflux (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR plays a key role in the process of normal esophageal epithelial cell carcinogenesis. BE tissue may originate from esophageal squamous cells (12). Long-term exposure of squamous cells to bile and gastric Role of epidermal growth factor receptor tyrosine kinase inhibitors in the treatment of esophageal carcinoma and the suggested mechanisms of action (Review)…”
Section: Egfr and Barrett's Esophagusmentioning
confidence: 99%